PERBANDINGAN METODE AUTOREGRESI DAN AUTOKORELASI SERTA SINGLE EXPONENTIAL SMOOTHING - Aprilia Ummi Mujahidah; Wellie Sulistijanti (Universitas Muhammadiyah Semarang, 2017)
Saripetojo Ice factory was founded in 1923 and produce ice to meet household needs as well as the preservation of fish, of which most is Cilacap Regency sea. This research aims to predict sales of ice in an ice Factory Saripetojo Cilacap in 2017. By using the method of forecasting method Autoregresi and Autocorrelation and Single Exponential Smoothing. The data used in this study as many as 84 of data from January 2010 until December 2016. From the results of research using the method of Autoregresi and Autocorrelation within one period producing the equation Autoregresi is better than Single Exponential Smoothing method with a value of 11568614 MSE. Based on the Autoregresi equation is obtained the highest occurring forecasting in December that is of low beams and 23524 occurred in January, namely of 18770 beams.Keywords: Autoregresi and autocorrelation, MSE, Single Exponential Smoothing